2012
DOI: 10.1127/0941-2948/2012/368
|View full text |Cite
|
Sign up to set email alerts
|

Weather patterns and hydro-climatological precursors of extreme floods in Switzerland since 1868

Abstract: The generation of 24 extreme floods in large catchments of the central Alps is analyzed from instrumental and documentary data, newly digitized observations of precipitation (DigiHom) and 20 th Century Reanalysis (20CR) data. Extreme floods are determined by the 95 th percentile of differences between an annual flood and a defined contemporary flood. For a selection of six events between 1868 and 1910, we describe preconditioning elements such as precipitation, temperature, and snow cover anomalies. Specific w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 21 publications
6
93
0
1
Order By: Relevance
“…In the case of the WPEs, we conclude that the Alpine inflow takes place at the southern or southeastern side of the Alps, which is supported by the mostly southerly located precipitation amounts. These features are similar to the "Canarian Trough" described by Stucki et al (2012) in association with past extreme floods in Switzerland. These cyclones are strongly influenced by a low over Brittany and thus show a southwesterly flow (Stucki et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the case of the WPEs, we conclude that the Alpine inflow takes place at the southern or southeastern side of the Alps, which is supported by the mostly southerly located precipitation amounts. These features are similar to the "Canarian Trough" described by Stucki et al (2012) in association with past extreme floods in Switzerland. These cyclones are strongly influenced by a low over Brittany and thus show a southwesterly flow (Stucki et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, most of the precipitation falls on the northern to northeastern side of the Alps. Similar situations (pivoting cut-off) have been found by Stucki et al (2012) in the context of past extreme floods in Switzerland. Hereby the cutoff low is located over the Adriatic Sea and is near-stationary due to blocking surface highs, located over western and eastern Europe.…”
Section: Discussionsupporting
confidence: 76%
“…The foehn storm of 15 February 1925 ranks among the most hazardous windstorms in Switzerland since the mid-nineteenth century (Stucki et al 2014). Substantial documentation is available on the associated damage (Fig.…”
Section: Documentary Weather and Loss Reconstructionmentioning
confidence: 99%
“…The 20CR has proven to be reliable for analyzing synoptic-scale, midlatitude weather systems Stucki et al 2012;Trigo et al 2014). Going one step further, Michaelis and Lackmann (2013) In the reanalysis, a deep surface low is located over Great Britain and surface air pressure increases toward southeastern Europe at 0000 UTC on 15 February 1925 (Fig.…”
Section: Documentary Weather and Loss Reconstructionmentioning
confidence: 99%
“…They however also found that, although flash floods are more frequent after wet antecedent conditions in central Europe, they primarily occur following dry conditions in the Mediterranean region and show no dependence on the antecedent conditions in the Alpine-Mediterranean region. For large Swiss lakes and streams, Stucki et al (2012) underline the importance of high soil saturation due to excessive water supply by enhanced melt and precipitation over several months for the generation of historical floods.…”
Section: P Froidevaux Et Al: Flood-triggering Precipitation In Switmentioning
confidence: 99%